GQAL: from rhetoric to reality - Farashuddin, Fehmin; Khan, Mahmuda Rahman; Mannan, Manzurul; Akter, Shahnuz; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
BRAC's Gender Quality Action Learning (GQAL) Progranune was initiated in 1994 to improve the quality of programmes with village women and to improve the quality of . gender relations within BR.AC. In its first year of intervention, GQAL covered 28 area offices of BRAC's Rural Development Programme and 8 area offices of the Health and Population Division. This short term process documentation of the GQAL programme aimed at finding out whether GQAL's operations have reflected its stated objectives; whether the gend~essages in GQAL 's documents have been reflected in its operations and what the Strel\:,oths and weaknesses of the programme are after its first year of operation. Information for the study was collected through re'\liew of GQAL documents, discussions with members of the Core Gender Team, participant observation of GQAL intervention sessions in area offices, group discussions and infonna.l interviews with area office staff participating in GQAL, and participant observation of GQAL facilitators' monthly meetings. Since this was not an evaluation of the programme, no recommendations have been made. However, several implications for future action have been identified, as follows: GQAL has created a forum for discussion but it needs to . specify whether this is solely a 'gender' forum and whether there are mechanisms for institutionalizing this forum. The GQAL manual provides many useful •gender' messages, but these messages should be made more specific to the context of BRAC. The GQAL programme is ideally a gender redistributive / transformative form of training. But can it bring about significant changes within the existing context of programme concern? In its :first year of interventions, GQAL focussed primarily on its second goal, that of improving gender relations within BRAC. It is now time for GQAL to address its first goal, that of improving quality of programme with village women and it needs to specify what measures will be undertaken to carry out this goal. Finally, GQAL needs to address the important issue of whether all issues are gender issues and whether GQAL is sufficient in itself to address all such issues.